2022
DOI: 10.1371/journal.pone.0268513
|View full text |Cite
|
Sign up to set email alerts
|

The influence of variations in background noise on Florida manatee (Trichechus manatus latirostris) detection of boat noise and vocalizations

Abstract: A manatee’s primary modality to detect a vessel on a possible collision course is hearing as underwater visibility is limited in many manatee habitats and their visual acuity is poor. We estimate a Florida manatee’s ability to detect the sound of an approaching boat and vocalizations in four different soundscapes in Sarasota Bay, FL. Background noise samples were collected every 5 minutes for a two-week period during winter and summer at each location (2019 or 2020). Sound levels in third octave bands (0.5, 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Similar adjustments in vocalization rates have been reported for dolphins (Tursiops truncatus) PLOS ONE [51] and humpback whales [52] in the presence of small crafts. Boat noise in manatee habitats varies by location and can reduce manatee communication space [53]. Manatees in our study may have compensated for boat presence by increasing vocal effort.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Similar adjustments in vocalization rates have been reported for dolphins (Tursiops truncatus) PLOS ONE [51] and humpback whales [52] in the presence of small crafts. Boat noise in manatee habitats varies by location and can reduce manatee communication space [53]. Manatees in our study may have compensated for boat presence by increasing vocal effort.…”
Section: Discussionmentioning
confidence: 64%
“…Foraging may also play a role in how sites are used. As suggested by Self-Sullivan et al ( 2003) [53] seagrass beds surround both sites, providing extensive foraging habitat for manatees. Studies of movements of GPS tagged Antillean manatees indicated they forage at different locations within a small geographic range (4-6 km) [56].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The anecdotes on anti-predator behavior might yield some insights to the degree that responses to vessels might be similar to responses to potential predators. Rycyk et al (2022) have recently reported acoustic differences in local habitats that might affect responses to vessels through differential sound transmission, but more work remains to be done to explain manatee behavioral variability.…”
Section: Discussionmentioning
confidence: 99%
“…Given their apparent cognitive flexibility and good hearing, why are the same manatees repeatedly struck by boats? Studies of masking by multiple boats and the effects of the acoustical environment (e.g., Rycyk et al, 2022) are needed to address this question.…”
Section: Discussionmentioning
confidence: 99%